The relation between 21st-century skills and digital skills: A systematic literature review - van Laar, Ester; van Deursen, Alexander J.A.M.; van Dijk, Jan A.G.M.; de Haan, Jos (Computers in human behavior, 2017)
Innovation starts with people, making the human capital within the workforce decisive. In a fast-changing knowledge economy, 21st-century digital skills drive organizations' competitiveness and innovation capacity. Although such skills are seen as crucial, the digital aspect integrated with 21st-century skills is not yet sufficiently defined. The main objectives of this study were to (1) examine the relation between 21st-century skills and digital skills; and (2) provide a framework of 21st-century digital skills with conceptual dimensions and key operational components aimed at the knowledge worker. A systematic literature review was conducted to synthesize the relevant academic literature concerned with 21st-century digital skills. In total, 1592 different articles were screened from which 75 articles met the predefined inclusion criteria. The results show that 21st-century skills are broader than digital skills – the list of mentioned skills is far more extensive. In addition, in contrast to digital skills, 21st-century skills are not necessarily underpinned by ICT. Furthermore, we identified seven core skills: technical, information management, communication, collaboration, creativity, critical thinking and problem solving. Five contextual skills were also identified: ethical awareness, cultural awareness, flexibility, self-direction and lifelong learning. •Conducted a systematic literature review to examine 21st-century digital skills for work.•1592 different articles were screened from which 75 articles were included.•21st-century skills are broader and more often on conceptual level than digital skills.•We propose a framework of 7 core and 5 contextual 21st-century digital skills.